Short-and Long–Term Follow–up in the Elderly Patients With ST–Elevation Myocardial Infarction Receiving Primary Angioplasty or Thrombolytic Therapy - Kazemi, Mohammad Kazem; Alimohammadzadeh, Khalil; Maher, Ali (International Journal of Cardiovascular Practice, 2019)
Introduction: The ischemic time serves as the most important parameter for treatment choice in patients with ST–elevation myocardial infarction (STEMI). The current study aimed at comparing the short– and long–term follow–up of elderly patients with STEMI undergoing primary angioplasty (PCI) or thrombolytic therapy.Methods: The current cross sectional study was conducted on all patients aged >65 years, admitted to the emergency department of Imam Hossein Hospital, Tehran, Iran from January 2014 to July 2016, diagnosed with STEMI . The demographics, medical history, family history, and mediation history were recorded for all patients. Patients received PCI or thrombolytic therapy based on the ischemic time and the treatment outcome and the following events were recorded. Patients were contacted after six months and data of their death or used treatments were recorded. All data were compared between the groups.Results: Of all patients, 38 subjects received thrombolytic therapy and 62 PCI. There was no significant difference between the groups in terms of mean age and gender (P=0.5 and 0.1, respectively). The frequency of positive medical history and smoking did not differ between the groups. There was no difference in the mean values of vital signs or serum parameters, mean ischemic time, left ventricular ejection fraction (LVEF), frequency of pulmonary emboli, cardiogenic shock, the involved vessel, and post-treatment complications between the groups (P>0.05). Of the 14 cases that died after six months, five were in the thrombolytic therapy group and nine in the PCI group (P=0.8). Mean hospital stay was not different between the groups (P=0.5).Conclusions: The results of the present study on two groups with similar demographics showed no significant difference between the groups in terms of the short– and long–term follow–up of PCI and thrombolytic therapy. The results indicated the appropriateness of treatment choice based on ischemic time and the available methods.